A microfluidic analysis of thrombus formation in reconstituted whole blood samples comparing spray‐dried plasma versus fresh frozen plasma. Issue 5 (5th December 2020) - Bercovitz, Rachel S.; Drew, Caleb S.; Bushee, Chana L.; Popovsky, Mark A.; Friedman, Kenneth D.; Anani, Waseem Q.
Abstract : Background: Prompt resuscitation with plasma and other blood products reduces trauma‐related morbidity and mortality. Standard storage and preparation techniques for frozen plasma limit its utility in the pre‐hospital setting. Plasma can be dehydrated using hot air (spray‐dried plasma), stored at room temperature and rehydrated quickly for use. The spray‐dry process decreases high‐molecular‐weight multimers of von Willebrand factor compared with conventional plasma. The objective of this study was to compare platelet adhesion and thrombus formation in a microfluidic perfusion assay facilitated by spray‐dried compared with frozen plasma using a non‐inferiority design. Study Design and Methods: Whole blood was centrifuged to obtain red cell concentrate, and a platelet pellet that was suspended in either spray‐dried or frozen plasma to create recombined whole blood. Platelets were fluorescently labelled, and samples were flowed through a collagen‐coated microchannel. Surface area coverage by platelets and thrombi was analysed and compared between each spray‐dried and frozen plasma pair. Results: Compared with whole blood samples containing frozen plasma, samples with spray‐dried plasma had similar surface area coverage of platelets and thrombi after 180 s of flow. Even when diluted with von Willebrand factor‐free plasma, there was no reduction thrombus formation. Conclusion: Spray‐dried plasma is not inferior in supporting haemostasis compared with fresh frozen plasma in a paired analysis. It offers advantages with respect to portability and ease of preparation over frozen plasma in the pre‐hospital setting. This study supports development of clinical studies to evaluate the efficacy and safety of spray‐dried plasma in trauma patients.